Phytobiotics blend as a dietary supplement for Nile tilapia health improvement. Issue 114 (July 2021) - Estaiano de Rezende, Renata Antunes; Soares, Michelly Pereira; Sampaio, Fernanda Garcia; Cardoso, Israel Luz; Ishikawa, Márcia Mayumi; Lima Dallago, Bruno Stéfano; Rantin, Francisco Tadeu; Teixeira Duarte, Marta Cristina
Abstract: Functional additives of natural origin included as dietary supplements have become an alternative to synthetic antibiotics to improve health and resistance to ecologically correct pathogenic diseases in fish farming. We tested whether incorporating a mixture of phytobiotics such as volatile oils of thyme, red thyme and pepper rosemary into the diet improves growth performance, oxidative stress, immune and hematological responses and resistance of juvenile Nile tilapia when subjected to a challenge with Aeromonas hydrophila compared to a synthetic antibiotic (enrofloxacin). The experimental design was completely randomized with three experimental groups: control diet, diets containing a mixture of thyme phytobiotic essential oils, red thyme and pepper rosemary (FTB) and the synthetic antibiotic enrofloxacin (ATB), with four replicates (14 fish per repetition/experimental unit). Plasma glucose levels, leukocyte respiratory activity, serum lysozyme levels, number of circulating erythrocytes and leukocytes, levels of lipid peroxidation (LPO), catalase (CAT) and glutathione S-transferase (GST) activity at the end of 20 days of feeding (phase) were evaluated and 24 h after exposure to bacteria (phase II). The supplementation of FTB and ATB did not change the performance parameters, but it was sufficient to increase lysozyme, leukocytes, neutrophils and monocytes after the bacterial challenge, reduction of CAT and LPO activity and the highest GST activity (P < 0.05). The results of the present study suggest that FTB as a dietary supplement has benefits and can replace synthetic ATB, including supplementation with FTB for 20 days to provide greater antioxidant protection in Nile tilapia, mitigate the impacts of stressors and modulate immunity, providing to fish greater resistance and protection against diseases. Highlights: Feeding supplemented with a blend of phytobiotics has increased the innate immunity of Nile tilapia and can replace the synthetic antibiotic enrofloxacin. Supplementation with a blend of phytobiotics for 20 days provides greater antioxidant protection in Nile tilapia. The blend of phytobiotics ensured a better ability of Nile tilapia to deal with infection by Aeromonas hydrophila.